Virtual screening of bioactive compounds from the lamiaceae family as acetylcholinesterase inhibitors for alzheimer’s disease - Noviardi, Harry; Utami, Mega; Masaenah, Eem (Pharmaciana, 2025)
Alzheimer's disease is a progressive neurological disorder that can impact adults aged 65 and beyond. A primary factor contributing to Alzheimer’s is the diminished availability of the neurotransmitter acetylcholine in the brain. Plants from the Lamiaceae family have been believed to possess potential as acetylcholinesterase inhibitors (AChEI) that can alleviate the symptoms of Alzheimer’s disease. This study aims to find possible bioactive compounds from plants of the Lamiaceae family, specifically Salvia officinalis L., Salvia lavandulifolia Vahl., Rosmarinus officinalis L., Collinsonia canadensis L., and Melissa officinalis L., as acetylcholinesterase inhibitors using in silico approaches. Active compounds from the Lamiaceae family were evaluated based on physicochemical properties, toxicity, Gibbs free energy (∆G), inhibition constant (Ki), absorption, excretion, metabolism, distribution, and molecular dynamics. From a total of 1,370 compounds derived from Lamiaceae plants, the compound 3,5,5-Trimethyl-4-[3-[3,4,5-trihydroxy-6-(hydroxymethyl) oxan-2]-yl]oxybut-1-enyl] cyclohex-2-en-1-one (TOC) from Salvia officinalis L. exhibited potential as an AChEI, possessing a molecular weight of 370 Daltons, 4 hydrogen donors, 7 hydrogen acceptors, a Log P partition coefficient of 3.46, a molar refractivity of 100, a Gibbs free energy change (∆G) of -11.2 kcal/mol, an inhibition constant (Ki) of 0.981 μM, and a total energy calculated via Molecular Mechanics Generalized Born Surface Area of 31.381 kcal/mol. In silico, the TOC ligand inhibits acetylcholinesterase to treat Alzheimer's.